Computerized analysis of erythrocyte aggregation from sequential video-microscopic images under gravitational sedimentation - Jayavanth, Sanjay; Singh, Megha (Innovation et technologie en biologie et médecine, une revue de technologie biomédical, 2004)
The erythrocytes form chain-like aggregates during sedimentation under gravitational field. The dynamic images of these are obtained by video-microscopic system by placing the erythrocyte suspension in plasma at hematocrit 5%, in a glass chamber of thickness 100 μm. The images at intervals of 2 min for 30 s duration are recorded. As the images are associated with high background noise, after digitization they are preprocessed for illumination correction, video de-interlacing, background subtraction, and deblurring, followed by post-processing involving edge enhancement, thresholding, median filtering and edge detection. By processing these images, to quantify the aggregation process, the morphometric parameters—projected aggregate area (PAA), projected aggregate perimeter (PAP) and form factor (FF), and sedimentation completion time (SCT) are obtained. To determine the variability of erythrocyte aggregation during human aging by this technique, blood samples from subjects of various age groups (from 20 to 60 years) are analyzed. The data obtained show the variability in the formation of aggregates in different age groups. The comparison in subjects of different age groups shows that the PAA, PAP and FF, and SCT are decreased significantly compared to that of subjects of age group 20–30 years. In subjects of 51–60 years, the formed aggregates are compact, which sediment faster compared to that of other age groups. Les érythrocytes forment des chaînes d’ agrégats lorsqu’ils sédimentent sous l’action de la gravité. Des images dynamiques sont obtenues par un système vidéo-microscopique en plaçant la suspension d’érythrocyte dans un plasma à 5% d’hématocrite à l’intérieur d’une chambre de verre de 100 μm d’épaisseur. Les images sont enregistrées pendant30sec à 2 minutes d’intervalle. Après numérisation, les images fortement bruitées sont traitées pour les corriger de leurs défauts de luminance, d’entrelacement vidéo et de bruit de fond. Un post-traitement est appliqué pour rehausser et détecter les contours. Pour mesurer le processus d’agrégation, des paramètres morphométriques sont étudiés: aire projetée de l’agrégat (PAA), périmètre projeté de l’agrégat (PAP), facteur de forme (FF), temps de sédimentation (SCT). Pour déterminer la variabilité de l’agrégation érythrocytaire avec le vieillissement, des échantillons de sang provenant de sujets d’âge divers (20 à 60 ans) sont analysés. L’analyse montre que les PAA, les PAP et les FF, et les SCT diminuent avec l’age surtout chez les sujets de 51-60 ans pour lesquels les agrégats formés sont compacts et sédimentent plus rapidement.